2015
DOI: 10.1155/2015/735418
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Variation in Fruit Morphology among Provenances ofSclerocarya birrea(A. Rich.) Hochst.

Abstract: Sclerocarya birrea (A. Rich.) Hochst. is a multipurpose fruit tree which is very useful in providing food security and meeting nutritional and economic needs. This study was conducted to assess eighteen provenances of Sclerocarya birrea planted in Mangochi, Malawi. The trial was assessed for fruit traits at fifteen years of age. There were significant ( < 0.001) variations among the provenances in number of fruits, fruit weight, pulp weight, seed weight, fruit length, and diameter. Magunde provenance from Moza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
44
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 12 publications
7
44
1
Order By: Relevance
“…Most accessions were genetically distinct, reflecting the tree-to-tree variation in morphological traits reported for S. birrea [14,16,20]. This high genetic variation among the studied accessions is because they are half-sibs that share genetic information from only one parent.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Most accessions were genetically distinct, reflecting the tree-to-tree variation in morphological traits reported for S. birrea [14,16,20]. This high genetic variation among the studied accessions is because they are half-sibs that share genetic information from only one parent.…”
Section: Discussionmentioning
confidence: 68%
“…The provenance trial data have shown great variability in morphological traits across populations [14,16,20]. The mother trees were characterized using RAPD [9] and showed significant variation within and among the populations.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the seed size, related to genetics other than indicated by clones, is also shown by the relation of seed size and provenance, for instance on Jatropha curcas (Guan et al 2013), Adansonia digitata L. (Munthali et al 2012). Sclerocarya birrea (Mkwezalamba et al 2015) and Faidherbia albida. (Fredrick et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic factor is also indicated by some studies which were exploring the relationship of seed size and provenance (Ager and Stettle 1983;Singh et al 2011;Munthali et al 2012;Shankar and Synrem 2012;Munthali et al 2012;Guan et al 2013;Abdelbasit et al 2014;Fredrick et al 2015;Mkwezalamba et al 2015). Some characteristics of fruit and seed are influenced by environmental factors too, such as altitude, temperature and agronomic practices (Quarda et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Since the establishment of the International Provenance trial of S. birrea, published papers on survival percentage [11], vegetative growth and fruit production [6,12,13], morphometric fruit traits [5], have been written on the trial. But no study has been conducted on the trial to address issues of phenology.…”
mentioning
confidence: 99%